Hyaluronan-Binding Protein Promotes Fibroblast Transformation and Heart Failure by Modulating the STAT5A–MMP13 Pathway - Hui Yan; Bing Huang; Bofang Zhang; Yunyao Li; Qiping Zhou; Ayipali Abudoureyimu; Guiqiu Cao; Hong Jiang (Biomedicines, 2025)
Background: Adverse cardiac remodeling drives heart failure progression, but the role of hyaluronan-binding protein (HYBID) in this process remains unclear. This study investigated the role of HYBID as a key profibrotic factor in the progression of adverse cardiac remodeling with a focus on its functional impact on cardiac fibroblasts and underlying molecular mechanisms. Methods: RNA sequencing analysis was employed to identify differentially expressed genes in mouse ventricular tissue post-myocardial infarction (MI). Fibroblast-specific genetically modified mouse models (knockdown and overexpression) were generated using FSP1 promoter-driven adeno-associated viruses. Comprehensive histological and biochemical assessments were conducted both in vivo and in vitro to evaluate the effects of HYBID modulation on cardiac remodeling. Molecular docking and immunoprecipitation assays were utilized to elucidate the mechanistic interactions between HYBID and its downstream targets. Results: RNA sequencing revealed HYBID as a fibroblast-enriched protein significantly upregulated in myocardial tissue of MI mice. Fibroblast-specific knockdown of HYBID attenuated MI-induced fibroblast activation, improved cardiac function, and mitigated adverse cardiac remodeling. Conversely, HYBID overexpression exacerbated fibroblast activation and promoted cardiac remodeling. Mechanistically, HYBID was found to competitively bind to STAT5A, thereby inhibiting the anti-fibrotic effects of MMP13 and driving fibroblast activation and adverse remodeling post-MI. Conclusions: Our findings establish HYBID as a novel fibroblast-enriched regulator that exacerbates fibrosis and adverse cardiac remodeling following MI. By uncovering the HYBID–STAT5A–MMP13 axis as a critical signaling pathway, this study provides new insights into the molecular mechanisms underlying heart failure progression.